Thermal performance of rotating latent heat systems with solar-optimized fractal tree fins - Yetao Xiang; Wanli Wang; Qunfeng Gu; Dongxia Li; Zengkui Xie (Case Studies in Thermal Engineering, 2025)
This study investigates a rotating tree-shaped fin latent heat storage system to enhance its thermal energy storage performance. A fractal design based on the Fibonacci sequence is applied to the tree-shaped fins and compared with conventional fins of the same volume fraction. The melting and solidification behaviors under rotational conditions are investigated, emphasizing the influence of rotational speed, thermal boundary temperature, and fin material properties on critical performance metrics such as thermal storage capacity, energy density, and phase change rate. The results demonstrate that the Fibonacci-based fractal design increases the contact area with the phase change material, accelerating melting. Rotation significantly improves phase transition efficiency: elevating the speed from 0 to 0.15 rpm increases TES capacity by 12.45 % while cutting melting duration by 45.86 %. However, when the speed rises from 0.05 rpm to 0.15 rpm, the average PCM temperature decreases by 2.23 %, the released heat drops by 26.86 %, and the complete solidification time is reduced by 66.67 %. Additionally, higher heat exchange temperatures elevate PCM temperature and stored heat while shortening melting duration. The thermal conductivity of fin materials also plays a critical role—copper fins significantly outperform steel fins in enhancing PCM thermal storage performance.